Kajian Potensi Pengolahan Sampah (Studi Kasus : Kampung Banjarsari ) - Enny Widawati; Harlianto Tanudjaja; Isdaryanto Iskandar; Carlos Budiono (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2014)
Garbage are the result of human activity, whether in the form of solid, liquid and gas. Garbage are a common problem faced by the Government. Up to now, a heap of trash becomes a problem which cannot be resolved by the Government. There are some common activity in managing waste such as reuse, composting and landfill. The result obtained from this waste management study in kampung banjarsari are divided by two criteria, priority and weighted. In the priority aspect was found that social aspect has priority of 0,203, economical aspect has priority of 0,106, on the other hand, in the weighted aspect was found that environmental aspects having weight of 0,597 and the technical aspects having weight of 0,094. The results obtained from the calculation of alternative waste treatment technologies reuse equal to 0,485, composting equal to 0,278, and landfill equal to 0,237. From the above, the best waste treatment is reuse